2020
DOI: 10.36660/abc.20190201
|View full text |Cite
|
Sign up to set email alerts
|

Ablação por Cateter sem Uso de Raios X para Tratamento de Fibrilação Atrial e Arritmias Atriais

Abstract: Background: Chemotherapy-related coronary artery disease (CAD) is becoming an emerging issue in clinic. However, the underlying mechanism of chemotherapy-related CAD remains unclear. Objective: The study investigated the association between chemotherapy and atherosclerotic anatomical abnormalities of coronary arteries among lung cancer patients.Methods: Patients undergoing coronary angiography (CAG) between 2010 and 2017, who previously had lung cancer, were examined. Risk factors associated with CAD and infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Malignancy is considered an independent predictor of increased risk of repeated revascularization and intrastent thrombosis in patients with prior percutaneous coronary intervention (PCI)( 8 ). Moreover, it has been shown that there is a higher atherosclerotic burden (as assessed by a higher SYNTAX score) with a high prevalence of complex lesions frequently located in the proximal segments of the coronary tree ( 47 , 48 ). Figure 1 summarizes the risk factors, pathophysiology and therapeutic management of ACS in cancer patients.…”
Section: Cardiotoxicity: Chemotherapy and Radiotherapymentioning
confidence: 99%
“…Malignancy is considered an independent predictor of increased risk of repeated revascularization and intrastent thrombosis in patients with prior percutaneous coronary intervention (PCI)( 8 ). Moreover, it has been shown that there is a higher atherosclerotic burden (as assessed by a higher SYNTAX score) with a high prevalence of complex lesions frequently located in the proximal segments of the coronary tree ( 47 , 48 ). Figure 1 summarizes the risk factors, pathophysiology and therapeutic management of ACS in cancer patients.…”
Section: Cardiotoxicity: Chemotherapy and Radiotherapymentioning
confidence: 99%